PENGARUH GROWTH OPPORTUNITY DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2016-2020 - Rahmawati, Eka Ayu; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Economic growth is a tool to measure the progress of a country which can be measured from the production sector. Food and beverage companies are growing rapidly and are expected to meet the daily needs of the community. The purpose of this study was to analyze and test the effect of Growth opportunity and Leverage on firm Value through capital structure. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used is purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that Growth opportunity has a significant negative effect on capital structure, Growth opportunity has a positive but not significant effect on firm Value, Leverage has a significant positive effect on capital structure, Leverage has a significant positive effect on firm Value, and structure capital has a significant negative effect on firm Value, Growth opportunity on firm Value through capital structure has a significant positive effect, Leverage on firm Value through capital structure has a significant negative effect.